A rapid and sensitive LC–ESI-MS/MS method for the detection of YF-49–92.MLS in rat plasma. (October 2013) - Gao, Qin; Huang, Xin; Jiang, Zhenzhou; Liu, Guanlan; Xiao, Yi; Sun, Lixin; Wang, Tao; Zhang, Luyong; Xie, Shaofei; Huang, Haiyan
Background: YF-49–92.MLS is a novel candidate for TB treatment. An accurate, precise and specific LC–MS/MS method for the quantification of YF-49–92.MLS in rat plasma using verapamil as an IS is reported in this paper.Methodology: Proper retention time and excellent peak shape were acquired using an Agilent Zorbax ® SB-C18 column with the mobile phase of 5 mmol/l ammonium acetate, 0.1% formic acid–methanol (30:70, v/v). The LLOQ was 1 ng/ml. The calibration curves encompassed concentrations from 20 to 5000 ng/ml. Intra- and inter-assay precision and accuracy were within 15% by determining low, medium and high concentration samples. Extraction recovery, stability, and matrix effects were also fully validated.Conclusion: This method has been validated to be rapid and sensitive, and successfully applied to the PK study of YF-49-92.MLS in rat plasma.